Similarities and differences of 137Cs distributions in the marine environments of the Baltic and Black seas and off the Fukushima Dai-ichi nuclear power plant in model assessments. (October 2018) - Maderich, V.; Bezhenar, R.; Tateda, Y.; Aoyama, M.; Tsumune, D.
Abstract: The compartment model POSEIDON-R with an embedded food web model was used to assess 137 Cs distributions in the Baltic and Black seas and off the Pacific coast of Japan during 1945–2020 due to the weapon testing and accidents at the Chernobyl and Fukushima Dai-ichi nuclear power plants. The results of simulations conducted with generic parameters agreed well with measurements of 137 Cs concentrations in the water, bottom sediments, and in fish. In the Black and Baltic seas, salinity variations affected the transfer of 137 Cs through the food web. The contamination of pelagic fish followed the water contamination with some delay, whereas demersal fish depuration was found to be related to decreasing 137 Cs concentrations in the upper sediment layer. On the Pacific shelf off Japan, intensive currents and eddies caused the simulated depuration rates in fish to be one-two orders of magnitude larger than those in the semi-enclosed Black and Baltic seas. Highlights: We applied box model with a dynamical food-chain model to three marine environments. The transport and fate of 137 Cs were simulated for the 1945–2020 including major Chernobyl and Fukushima nuclear accidents. The contamination in the pelagic fish followed the water contamination with some delay. Depuration rates in demersal fish were obtained similar to the upper layer of bottom sediments. The salinity variations affected transfer of 137 Cs through the food web in the Black and Baltic Seas.